A life cycle assessment of Hydropower-Silicon-Photovoltaic industrial chain in China. (15th August 2022) - Shen, Zihuang; Ma, Lin; Yang, Yuchen; Fan, Mingyang; Ma, Wenhui; Fu, Ling; Li, Ming
Abstract: In this paper, we conducted a life cycle assessment (LCA) for the Hydropower-Silicon-Photovoltaic (HSPV) industrial chain in China. The Energy Conservation and Emission Reduction Index in the 13th Five Year Plan of China (ECER-135) is calculated based on the software eBalancev4.7 (eB) and eFootprint (eF). The total environmental impact index of ECER-135 of the HSPV industrial chain is 2.61E-06. The uncertainty result of the comprehensive index is 15.21% and the uncertainty of the inventory data is no more than 30%. The Energy Payback Time (EPBT) of the HSPV industrial chain is calculated as 1.68 years, accounting for only 5.60% of the operating cycle of the PV station. There are 7 impact category indexes of ECER-135, which are Chemical Oxygen Demand (COD), Primary Energy Demand (PED), CO2, SO2, Ammonia Nitrogen Content (NH3 –N), NOx and Industrial Water Use (IWU). Considering the contribution of characteristic indexes to ECER-135, the contribution of PED index accounts for 22.93% of ECER-135, which is the major factor to environmental impact, and it is followed by COD, which accounts for 18.40%. Considering the contribution of each stage to ECER-135, PV module manufacturing, BOS manufacturing and SoG-Si manufacturing stages have significantly contributed to ECER-135, in which the PV module manufacturing stage has the greatest contribution to ECER-135, accounting for 97.63%, which is the main stage of impact on the environment. The sensitivity analysis reveals that the highest sensitivity is copper wire consumption, which is 47.83%. It is followed by aluminum consumption during the BOS manufacturing and the PV module manufacturing, which are 41.70% and 29.75% respectively. Finally, compared the total environmental impact of the HSPV industrial chain and the Thermalpower-Silicon-Photovoltaic (TSPV) industrial chain, the results reveal that the HSPV industrial chain has the energy-saving and emission reduction benefits of 2.89E-06, whose comprehensive indexes account for 47.39% of that of the TSPV industrial chain, proving that the HSPV industrial chain has significant energy saving and emission reduction benefits in all indexes. The EPBT of the HSPV industrial chain is only 38.17% of that of the TSPV industrial chain. Highlights: Conducting a life cycle assessment of Hydropower-Silicon-Photovoltaic(HSPV). The contribution, sensitivity and uncertainty analyses of HSPV were conducted. Serving as to put forward corresponding improvement measures. The results of Thermalpower-Silicon-Photovoltaic(TSPV) and HSPV were Compared. The Energy Payback Time of HSPV is only 38.17% of that of TSPV.